Catalytic performance and SO2 tolerance of tetragonal-zirconia-based catalysts for low-temperature selective catalytic reduction. Issue 17 (15th August 2016) - Liu, Rong; Ji, Lingchen; Xu, Yifan; Ye, Fei; Jia, Feng
Abstract: Abstract : MnO x –CeO2 /t-ZrO2 catalyst was prepared by impregnation of nanotetragonal zirconia. The NO conversion of 5 wt% MnO x –CeO2 /t-ZrO2 catalyst was 68.1% at 100 °C while that of 30 wt% MnO x –CeO2 /t-ZrO2 catalyst was 97.4%. The x-ray diffraction, Brunner–Emmet–Teller measurements (BET), and H2 -TPR showed surface properties of the prepared catalysts were good for selective catalytic reduction reactions. X-ray photoelectron spectroscopy analysis indicated that Mn 4+ and Ce 4+ oxidation states were predominant on the surface of the catalyst and so was lattice oxygen which was conducive to Lewis acid sites. NH3 -TPD test results demonstrated that Lewis acid sites are predominant on the surface of catalyst. The presence of SO2 reduced the catalyst activity. The realized conversion dramatically decreased to 47% from nearly 100% after 8 h. Characterization of fresh and spent catalysts indicated the deterioration of active component and deposition of NH4 HSO4 or (NH4 )2 SO4 contribute to SO2 poisoning.